2016
DOI: 10.1021/acs.langmuir.6b01058
|View full text |Cite
|
Sign up to set email alerts
|

How Peptide Molecular Structure and Charge Influence the Nanostructure of Lipid Bicontinuous Cubic Mesophases: Model Synthetic WALP Peptides Provide Insights

Abstract: Nanostructured bicontinuous lipidic cubic phases are used for the encapsulation of proteins in a range of applications such as in meso crystallization of transmembrane proteins and as drug delivery vehicles. The retention of the nanoscale order of the cubic phases subsequent to protein incorporation, as well as retention of the protein structure and function, is essential for all of these applications. Herein synthetic peptides (WALP21, WALPS53, and WALPS73) with a common α-helical hydrophobic domain, but vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…SANS was therefore used to examine the scattering of the transmembrane peptide WALP21 encapsulated within the contrast-matched cubic phases of PE. Previous research by us has shown that the purely hydrophobic WALP21 peptide does not have much effect on the diamond cubic Q II D phase lattice parameters of PE, presumably due to minimal hydrophobic mismatch between the cylindrically shaped peptide (∼31 Å long) and the lipid bilayer thickness (∼26 Å) …”
supporting
confidence: 91%
See 2 more Smart Citations
“…SANS was therefore used to examine the scattering of the transmembrane peptide WALP21 encapsulated within the contrast-matched cubic phases of PE. Previous research by us has shown that the purely hydrophobic WALP21 peptide does not have much effect on the diamond cubic Q II D phase lattice parameters of PE, presumably due to minimal hydrophobic mismatch between the cylindrically shaped peptide (∼31 Å long) and the lipid bilayer thickness (∼26 Å) …”
supporting
confidence: 91%
“…We suggest that the high viscosity of the gyroid cubic phase samples, combined with the extremely low hydration (13% w/w), has precluded peptide uptake in this case. The effect is exacerbated by the high lateral pressure profile for branched chain lipids such as PE, which may also cause slow equilibration of the samples . In this case the peptide may be present as microcrystals or clusters of peptide coexisting with, but not incorporated within, the gyroid cubic phase.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…A number of recent studies have therefore investigated changes to the lipidic nanostructure caused by the incorporation of amphiphilic proteins and peptides within the bicontinuous cubic phases. 1,[12][13][14][15][16][17] Hydrophobic mismatch, hydrophilic domain size and charge were found to be the most important factors affecting the nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…While spectroscopic techniques that investigate the conformation of the proteins have been used as an indirect measure for protein activity, 13,15,18,19 direct measurements of the activity of amphiphilic proteins within the bicontinuous cubic phase remain challenging. The enzyme activity of soluble oxidases in the nanoscale water channels of the cubic phase has been reported, for example for glucose oxidase, 10,20,21 ceruloplasmin, 20 lactate oxidase, 21 urease, 21 creatinine deiminase, 21 cholesterol oxidase, 10 horseradish peroxidase 22,23 and laccase.…”
Section: Introductionmentioning
confidence: 99%